1940 FDR, Willkie, Lindbergh, Hitler - the election amid the storm - Dunn, Susan 1945- (Yale Univ. Press, 2013)
The spellbinding story of the Roosevelt-Willkie election season, when bitterly divided Americans debated the fate of the nation and the world